1997
DOI: 10.1088/0953-2048/10/5/014
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of the Nd-123 phase in air with as high as 95 K

Abstract: The possibility of preparing bulk Nd-123 by the partial-melting technique in air is reported for the first time. The effects of the starting composition and of processing conditions (temperature, annealing time) on the superconducting properties of the system were investigated. The electrical properties were found to depend critically on the starting composition as well as on the annealing times and the cooling rates. The best results (zero-resistance temperature with an onset ) were obtained starting with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Recently Obradors et al [3] and Hu et al [4] have reported a high T C of 95-96 K obtained in airmelt-processed samples. In both cases, post annealing in argon at high temperature above 900 • C is necessary prior to oxygenation at low temperature [5]. However the fishtail effect in these samples was found to be lower than in OCMG samples.…”
Section: Introductionmentioning
confidence: 86%
“…Recently Obradors et al [3] and Hu et al [4] have reported a high T C of 95-96 K obtained in airmelt-processed samples. In both cases, post annealing in argon at high temperature above 900 • C is necessary prior to oxygenation at low temperature [5]. However the fishtail effect in these samples was found to be lower than in OCMG samples.…”
Section: Introductionmentioning
confidence: 86%
“…8 Reduction of temperature enhances the driving force of decomposition; however, its rate can be low because of extremely slow diffusion of components (the maximum rate of the process was experimentally observed at * 500 8C, see also S.3). The possibility for spinodal decomposi- tion to occur was inferred from the experimental results obtained for the specimens prepared by zone melting 91 and large-grain ceramics; 70,92 it was also postulated (based on the data on the equilibrium phase diagrams 80 ) for a model of a regular-type solution with a high positive energy of interaction between the components (* 40 kJ mol 71 ).…”
Section: B the Problem Of Low-temperature Decompositionmentioning
confidence: 99%
“…The anomalous peak effect phenomenon generally associated with outstanding magnetic and electric properties of NdBa 2 Cu 3 O 7 [1] is known to be the result of flux pinning on nanoscale compositional fluctuations formed in a supersaturated solid solution due to its subsolidus decomposition [2][3][4][5][6]. This is the most remarkable, but not the only, example among the other still puzzling consequences of collective cation and oxygen disorder influencing structural characteristics [7][8][9][10][11][12][13][14][15][16][17][18][19][20], superconductivity [1,3,6,10,11,[20][21][22][23][24], thermal stability [2, 5, 11-13, 25, 26], oxygen exchange features [14,19,22,23,26] and transformation dynamics [6,10,14,15,[21][22][23] of NdBCO HTSCs.…”
Section: Introductionmentioning
confidence: 99%
“…REE-barium cuprates melt-processed under special conditions form large-grain ceramics with effective pinning centres and suppressed substitution of Ba with Nd [1][2][3][4]6]. An analysis of low-temperature processes is also unavoidable [2,[10][11][12][13][14][15], however a few soft-chemistry works have only attempted the preparation of single-phase Nd123 below 850 • C [20,22,23,25,27].…”
Section: Introductionmentioning
confidence: 99%